A Comparison of Transradial and Transfemoral Access for Splenic Angio-Embolisation in Trauma: A Single Centre Experience. (March 2020) - Adnan, Sakib M.; Romagnoli, Anna N.; Martinson, James R.; Madurska, Marta J.; Dubose, Joseph J.; Scalea, Thomas M.; Morrison, Jonathan J.
Abstract : Objective: The study compared transradial access (TRA) and transfemoral access (TFA) for splenic angio-embolisation (SAE), with a focus on technical success, intra-operative adjuncts, and complications. Methods: This was a retrospective comparative study of all trauma patients undergoing SAE by TRA or TFA between February 2015 and February 2019 at a single institution. The medical records were queried for procedural and post-operative data, with comparisons made based on access site. Continuous variables were compared using a two tailed t test and categorical variables were compared using a chi square test. Results: Over a four year period, there were 47 cases of SAE via TRA and 127 via TFA. Technical success was 95.7% during TRA and 98.4% during TFA ( p = .30). Technical failures were a result of failed splenic artery cannulation after successful radial or femoral access. Time to splenic cannulation was shorter in the TRA group (19 min vs. 30 min; p = .008). Two or fewer catheters were used during TRA, whereas more than two catheters were needed during TFA ( p < .001). There were no statistically significant differences in procedure length, fluoroscopy time, radiation dose, or contrast volume between groups. Nine patients (5.2%) developed access related complications, all in the TFA group ( p = .12). Mortality rate was 2.3% ( n = 4), with no statistical significance between groups ( p = .71). Conclusion: While TFA is the conventional strategy for SAE, TRA is a safe and efficacious modality for SAE in trauma patients. Although larger studies are needed to establish the full efficacy of TRA for SAE at the multi-institutional level, this single centre study demonstrates the legitimacy of an alternative means for SAE in the trauma population.